2022
DOI: 10.1021/acs.biochem.2c00061
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Paraptosis by Cyclometalated Iridium Complex-Peptide Hybrids and CGP37157 via a Mitochondrial Ca2+Overload Triggered by Membrane Fusion between Mitochondria and the Endoplasmic Reticulum

Abstract: We previously reported that a cyclometalated iridium (Ir) complex-peptide hybrid (IPH) 4 functionalized with a cationic KKKGG peptide unit on the 2-phenylpyridine ligand induces paraptosis, a relatively newly found programmed cell death, in cancer cells (Jurkat cells) via the direct transport of calcium (Ca 2+ ) from the endoplasmic reticulum (ER) to mitochondria. Here, we describe that CGP37157, an inhibitor of a mitochondrial sodium (Na + )… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 120 publications
2
21
0
Order By: Relevance
“…Paraptosis is a type of programmed cell death (PCD) and is characterized by cytoplasmic vacuolation derived from the swelling of intracellular organelles such as mitochondria and the ER. We previously reported that IPHs 1 – 4 and celastrol (Scheme ), a triterpenoid isolated from Tripterygium wilfordii, induce paraptosis via an influx of Ca 2+ from the ER into mitochondria, the damage of organelles such as mitochondria, ER, and lysosomes, cytoplasmic vacuolization, ,,, as evidenced by the transmission electron microscopic (TEM) analysis and staining experiments with methylene blue . Thus, Jurkat cells were treated with syn- 6 or anti- 6 (5 μM) for 1 h at 37 °C under 5% CO 2 and fixed with glutaraldehyde and osmium tetroxide (OsO 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Paraptosis is a type of programmed cell death (PCD) and is characterized by cytoplasmic vacuolation derived from the swelling of intracellular organelles such as mitochondria and the ER. We previously reported that IPHs 1 – 4 and celastrol (Scheme ), a triterpenoid isolated from Tripterygium wilfordii, induce paraptosis via an influx of Ca 2+ from the ER into mitochondria, the damage of organelles such as mitochondria, ER, and lysosomes, cytoplasmic vacuolization, ,,, as evidenced by the transmission electron microscopic (TEM) analysis and staining experiments with methylene blue . Thus, Jurkat cells were treated with syn- 6 or anti- 6 (5 μM) for 1 h at 37 °C under 5% CO 2 and fixed with glutaraldehyde and osmium tetroxide (OsO 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned results strongly suggest that TPHs ( syn- 6 and anti- 6 ), like 4 , induce paraptotic cell death. Because it has recently been reported that the transport of Ca 2+ from the ER to mitochondria is crucial in paraptosis induced by IPHs, , we examined the concentrations of Ca 2+ in mitochondria and the cytosol by flow cytometric analysis (Figure a,b) . Jurkat cells were preincubated with Rhod-2/AM (5 μM), an indicator of mitochondrial Ca 2+ , or Rhod-4/AM (5 μM), an indicator of cytosolic Ca 2+ , for 30 min and then treated with syn- 6 or anti- 6 (5 μM) for given incubation times (0, 15, 30, 45, 60 min).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations